Contaminant diversity on Umiujaq territory, Nunavik, Canada - Herrmann, Thora; Joliet, Fabienne; Gigault, Julien; Gibaud, Manon; Coxam, Véronique; Chanteloup, Laine; Dervilly, Gaud; Bhiry, Najat; Cloutier, Danielle; Rollet, Anne-Julia; Funatsu, Beatriz M.; Decaulne, Armelle (CCSD, 2024)
International audience The quality of the Umiujaq socio-ecosystem is assessed by examining the presence of contaminants in its territory. Various objects are of crucial interest: (i) the landfill, (ii) the river, (iii) sediments in the watersheds, (iv) fish in the river and at its mouth, (v) bivalves in the coastal zone, (vi) but also the whole of the indigenous territory. Several samples of different materials were collected at varying distances from the village, in 2022 and 2023. Despite Inuit being peoples of the sea, discussions with local residents highlighted their interest in the watercourses and the resources they support. Results show that traces of contaminants are similar to those found in other Inuit communities in the polar regions. Here, we present the preliminary, multidisciplinary results obtained over the past year, along with the most recent fieldwork. An emic approach was used to raise the question of the edibility of local foods in the vicinity of the landfill, and to study disturbances induced by climate change, in addition to chemical contamination. Questioning the Inuit animist point of view has also shown that while the word "contaminant" does not exist in Inuktitut, its translation actually covers a diversity of meanings, including the notion of ideal contamination, such as the impact of colonization and the responsibilities attributed to it in the chain of contamination. One of the perspectives envisaged is to include the study of the transfer dynamics of these contaminants (i) by integrating meteorological data to target the preferential zones of fallout of contaminants from anthropogenic fumes, but also (ii) by studying the connectivity between the different compartments (e.g. slope - watercourse). La qualité du socio-écosystème d'Umiujaq est examinée à travers la présence de contaminants sur son territoire. Différents objets sont d'un intérêt crucial : (i) la décharge, (ii) la rivière, (iii) les sédiments dans les bassins versants, (iv) les poissons de la rivière, de ...